Development of Inquiry Based Learning Module Theme 4 (Rights and Obligations) to Improve Student Learning Outcomes - Alwa Mhd Tanzi Al-alang; Afdal; Fachri Adnan; Yeni Erita (Postgraduate, University of Mataram, 2023)
This article aims to develop an inquiry-based learning module for theme 4 to improve the learning outcomes of class V students on valid and practical rights and obligations material. This type of research is Research and Development (development research). This inquiry-based theme 4 learning module was developed using 4-D. The research was conducted in the odd semester of the 2023/2024 academic year. Data collection was carried out by validating the developed inquiry-based module trials. The inquiry-based module design which had been designed according to the inquiry learning steps was validated by five experts and then tested in class V at SDN 02 Gunung Tuleh to determine the practicality of the inquiry-based module being developed. From the results of the research conducted, it is known that the inquiry-based learning module for theme 4 to improve the learning outcomes of class V students on rights and obligations material is in the very valid category with an average validity percentage of 88.55%. The modules that have been developed are categorized as very practical by teachers with an average practicality percentage of 91.67%, and are also categorized as very practical according to students with an average practicality percentage of 97.18%. Based on the validity and practicality test, the theme 4 inquiry-based learning module was declared very valid, indicating that the module developed can improve the learning outcomes of class V students.